2021
DOI: 10.1519/jsc.0000000000003979
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Rich Water Consumption Positively Affects Muscle Performance, Lactate Response, and Alleviates Delayed Onset of Muscle Soreness After Resistance Training

Abstract: Hydrogen rich water consumption positively affects muscle performance, lactate response, and alleviates delayed onset of muscle soreness after resistance training. J Strength Cond Res 36(10): 2792-2799, 2022-Positive outcomes of hydrogen rich water (HRW) supplementation on endurance performance have been shown, but the effects of HRW in resistance training are unclear. The aim of this study was to assess the effects of 1,260 ml of HRW intake on physiological, perceptual, and performance responses to a resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(47 citation statements)
references
References 38 publications
2
41
0
4
Order By: Relevance
“…We expected the effect size in this study to be medium ( d = 0.8) based on the results of Botek et al [ 30 ]. An a priori power analysis with respect to paired two-tailed t-test and parameters set to α = 0.05 and β = 0.20 was performed using G*Power version 3.1.9.7 (Heinrich-Heine-Universität, Düsseldorf, Germany).…”
Section: Methodsmentioning
confidence: 86%
See 3 more Smart Citations
“…We expected the effect size in this study to be medium ( d = 0.8) based on the results of Botek et al [ 30 ]. An a priori power analysis with respect to paired two-tailed t-test and parameters set to α = 0.05 and β = 0.20 was performed using G*Power version 3.1.9.7 (Heinrich-Heine-Universität, Düsseldorf, Germany).…”
Section: Methodsmentioning
confidence: 86%
“…The dose relative to body mass was 10.2 ± 1.1 μmol kg −1 . This HRW hydration protocol included a 1-week washout period similarly to previous HRW studies [ 24 , 28 , 30 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Molecular hydrogen (H 2 ) has been shown to be a healthy, safe gas [ 20 ] with a strong and selective antioxidative capability for scavenging the harmful hydroxyl radical and peroxynitrite anion [ 20 , 21 ]. Numerous studies have indicated that H 2 has anti-inflammatory [ 22 ], anti-apoptosis [ 23 ], antifatigue [ 24 , 25 , 26 , 27 ], and regulatory properties [ 28 ]. Based on the reported beneficial health effects across a variety of diagnoses [ 22 , 29 ], H 2 administration has recently been proposed as a promising therapeutic gas for COVID-19 patients [ 7 , 30 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%